Novel aspects of the phosphorylation and structure of pathological tau: implications for tauopathy biomarkers - Taeko Kimura; Haruaki Sato; Maria Kano; Lisa Tatsumi; Taisuke Tomita (FEBS Open Bio, 2024)
The deposition of highly phosphorylated and aggregated tau is a characteristic of tauopathies, including Alzheimer's disease. It has long been known that different isoforms of tau are aggregated in different cell types and brain regions in each tauopathy. Recent advances in analytical techniques revealed the details of the biochemical and structural biological differences of tau specific to each tauopathy. In this review, we explain recent advances in the analysis of post‐translational modifications of tau, particularly phosphorylation, brought about by the development of mass‐spectrometry and Phos‐tag technology. We then discuss the structure of tau filaments in each tauopathy revealed by the advent of cryo‐EM. Finally, we describe the progress in biofluid and imaging biomarkers for tauopathy. This review summarizes current efforts to elucidate the characteristics of pathological tau and the landscape of the use of tau as a biomarker to diagnose and determine the pathological stage of tauopathy.